(untitled) (Journal of Economic Research & Business Administration, 2024)
Consumer spending represents one of the key drivers of economic growth in any country. In recent years, the share of real consumption expenditures in the aggregate income of Kazakhstan residents tends to grow. Given the existing differences in the growth of income of Kazakhstan citizens and prices for goods and services, it is actualized to study the impact of socio-demographic and financial factors on the ability to adjust consumption, as well as to assess the impact of economic shocks on the level of consumption in the short and long term. Thus, the purpose of the presented research is to study the contribution of influencing factors to the level of consumer spending of Kazakhstan citizens. The scientific significance lies in the confirmation of the hypothesis of constant income and refutation of the hypothesis of random walk on the example of consumers in Kazakhstan. The modified least squares method and the pooled group mean method were used to estimate the coefficients on the variables of interest in the short and long run. According to the results of the research, the growth of temporary incomes contributes to equalization of consumption of Kazakhstan residents only by 6% in the short term and by 22% in the long term. After accounting for influencing factors, the slope factor estimate decreased to 11% in the long run. The growth of savings of Kazakhstan citizens does not contribute to the adjustment of their consumption expenditures, as well as the employment shock and the growth of the average number of members in the household contributes to the reduction of consumption in the long run. Consequently, we can conclude that the households’ savings rate is insufficient. At the same time, an increase in the level of education can have a positive impact on smoothing the consumption of Kazakhstan citizens in the long term. It was also confirmed that households are more sensitive to spending on durable goods than on food items. The obtained results can be used in the development of a set of measures of state support of households in Kazakhstan, as well as in the course of microeconomics intermediate level as additional material to the topic "Theory of consumer behavior", which emphasizes the practical significance of the research. Key words: consumption, households, savings, employment shock, education.